2(5x-3)-1=13

Simple and best practice solution for 2(5x-3)-1=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5x-3)-1=13 equation:


Simplifying
2(5x + -3) + -1 = 13

Reorder the terms:
2(-3 + 5x) + -1 = 13
(-3 * 2 + 5x * 2) + -1 = 13
(-6 + 10x) + -1 = 13

Reorder the terms:
-6 + -1 + 10x = 13

Combine like terms: -6 + -1 = -7
-7 + 10x = 13

Solving
-7 + 10x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 10x = 13 + 7

Combine like terms: -7 + 7 = 0
0 + 10x = 13 + 7
10x = 13 + 7

Combine like terms: 13 + 7 = 20
10x = 20

Divide each side by '10'.
x = 2

Simplifying
x = 2

See similar equations:

| 6v+6=4v+2(v+3) | | 3.1-0.2a=1.5 | | m+m+5+m+8=84 | | 5-2p=7 | | -7.26+18p=6p-2.22+12.3p | | 3x+4y=75 | | 4x-48=36 | | 25.50x=12.50 | | -1=c-6 | | 6x+(3x-2)=14 | | -7v-5=-5v-9 | | x^2-7/3x-2/3 | | X+-5=6 | | -20+2x=30 | | 184=6y+4 | | -2n(9-10n)= | | 25.50=13.50 | | 8/3=32/x | | 6.2h+51.4h=4.8h+5 | | 6x+10=-7x-3 | | -2=a+6 | | 12(1)-4y=16 | | -5(-a-8)=16-a | | -17.7r=-16r+18.02 | | 7x+3y=-24 | | 12(0)-4y=16 | | 9+13x=35+26x | | -1/2(6-10x)+4=1/4(12x-20) | | 9x1/8 | | -12h+34=-4h-17 | | 4x+4=3-x | | 2x+(-3)=-9 |

Equations solver categories